Arterial trombozla gas6 (growth arrest- specıfıc gene 6) ve mgp (matrıks gla proteini) ilişkisi - Yılmaz, Erdem (My University, 2017)
Amaç: Ateroskleroz miyokard infarktüsü, inme, koroner ve periferik arter hastalıklarının patolojisinde rol oynayan en önemli faktörlerden biridir.

Purpose: Atherosclerosis is the most important factor that plays role in the pathology of myocardial infarction, stroke, coronary and peripheral arterial diseases.
Keywords: “Growth Arrest-Specific 6”; Ateroskleroz; Biyokimya; Growth Arrest-Spesific Protein 6; K vitamini; K Vitamini Atherosclerosis; Koroner hastalığı; Matrıks gla proteini; Matriks Gla Protein; Matrix Gla Protein; Proteinler; Sağlığa etkisi; Tedavi; Thromboembolism; Tıp; Tromboembolizm; Vitamin K